The making of global players: A look on Malaysian firms adopting e-commerce - Abu Bakar, Abdul Rahim; Hussin, Zolkafli; Hashim, Fariza (Universiti Utara Malaysia, 2002)
This study looks at the current initiatives by the private firms on the e-commerce projects in Malaysia. It seeks to identify the driving forces of private firms adopt e-commerce, to explore private firms initiatives and participation in e-commerce and finally to gauge the level of participation of the private firms in e-commerce. The findings provide interesting facts where Malaysian firms primarily SMEs possess a global market focus with the ability to transact electronically. Malaysian e-commerce firms have the capability to compete in the global digital marketplace together with other large firms from the developed countries mainly, the United States.